Genetic Diversity of 17 Autochthonous Italian Chicken Breeds and Their Extinction Risk Status - Soglia, Dominga; Sartore, Stefano; Lasagna, Emiliano; Castellini, Cesare; Cendron, Filippo; Perini, Francesco; Cassandro, Martino; Marzoni, Margherita; Iaffaldano, Nicolaia; Buccioni, Arianna; Dabbou, Sihem; Castillo, Annelisse; et al. (Frontiers in Genetics, 2021)
The preservation of genetic variability of autochthonous poultry breeds is crucial in global biodiversity. A recent report revealed small breed size and potential risk of extinction of all native Italian poultry breeds; therefore, a correct assessment of their genetic biodiversity is necessary for a suitable management of their preservation. In this work, we provided an overview of the contribution to poultry biodiversity of some Italian autochthonous breeds reared in conservation centers devoted to local biodiversity preservation . The level of genetic diversity, molecular kinship, inbreeding, biodiversity contribution and rate of extinction of each breed were analyzed with a set of 14 microsatellite loci in seventeen autochthonous chicken breeds. To evaluate the breed genetic variability, number (Na,) and effective number (Ne, richness allele) of alleles, observed (Ho) and expected (He) Heterozygosis and F index were surveyed. The contribution of each analyzed breed to biodiversity of the whole dataset was assessed using MolKin3.0; global genetic diversity and allelic richness contribution was evaluated. All the investigated loci were polymorphic; 209 alleles were identified (94 of which private alleles). The average number of alleles per locus was 3.62 and the allele richness was 2.27. The Ne resulted lower in all breeds due to the presence of low frequency alleles that can be easily lost by genetic drift, thus reducing the genetic variability of the breeds and increasing their risk of extinction. The global molecular Kinship was 27%, the average breed molecular kinship was 53%, and the mean inbreeding rate 43%, with a self-coancestry of 78% . Wright’s statistical analysis showed a 41% excess of homozygous due to breed genetic differences (34%) and to inbreeding within the breed (9%). Genetic variability analysis showed that 11 breeds were in endangered status. The contribution to Italian poultry biodiversity, estimated as global genetic diversity, ranged from 30.2% to 98.5%. In conclusion, the investigated breeds maintain a unique genetic pattern and play an important role in global Italian poultry biodiversity, providing a remarkable contribution to genetic variability.